Brisingr - Paolini, Christopher (RANDOM HOUSE London, 2009)
Brisingr: book three (the inheritance cycle), as the name suggests, is the third book in the inheritance cycle series by christopher paolini considered a worthy third installment to the series, the book takes the story forward after eragon and eldest and starts after about three days from where eldest closes the story is set in the fictional continent of alagaesia, circling around the lives of a teenage boy named eragon and his dragon saphirain this book, the protagonists eragon and saphira whisk past few sharp turns like helping roran save katrina from the ra$1 (Bzac, keeping varden unified and obeying nasuada, completing their training with the elves, undoing the spell on elva, supporting orik, and avenging hrothgar, garrow, and kvistorthe growing up story of a farm boy to fighting against the most dangerous enemies, the plot consists of endless revelations as it nears the end, and a final confrontation awaits the reader after all, eragon is the greatest hope to rid the land of tyranny, and the only one who can stand against the reign of king galbatorixbrisingr is a novel with superb battle descriptions, a realistic love story of an elf and a human, and extremely intelligent twists in the plot the book was published by rhuk in 2009 and is available in paperback key features: the book saw first day sales of 550,000 copies and debuted at number 1 on usa today$1 (Bs top 150 best-sellers lists